In-House Refurbishing and Outsourcing Refurbishing Models with Degree of Interchangeability in Product Design - Kurdhi, Nughthoh Arfawi; Vania, Kezia Abigail; Widyaningsih, Purnami; Sudibyo, Nugroho Arif (Universitas Muhammadiyah Mataram, 2023)
Refurbishing is the process of processing used products into products with the quality of new products. Refurbishing can be done by the manufacturer itself (in-house) or the manufacturer can delegate the refurbishing process to other manufacturers (outsourcing). This research aims to construct an in-house refurbishing model and an outsourced refurbishing model, determine the optimum solution, analysis, and application so that optimum benefits are obtained, and compare the in-house refurbishing model and the outsourced refurbishing model. Multivariable function optimization is used to get optimum profit. Judging from the optimum production results, manufacturers who carry out in-house refurbishing choose a higher degree of interchangeability and produce more new products. Products with an interchangeability design are products that can be used to replace similar products with the same function. Based on economic benefits, manufacturers who carry out in-house refurbishing get greater profits than outsourcing refurbishing. Viewed from environmental sustainability, outsourcing refurbishing is more environmentally friendly than in-house refurbishing.